FinTech - Decoding the effect of regulatory sandboxes in South Africa: a comparative study of the Financial Services Sector Laws in context - Dambuza, Tebogo (Department of Commercial Law, 2024)
This is a comparative study on the legal and regulatory framework in South Africa and the United Kingdom focused on the creation of the “regulatory sandboxes” in the financial sector. The study identifies the types of regulatory methods that can be effective in both jurisdictions. The focus is on the creation, implementation, and supervision of sandboxes, specifically with FinTech, and the successful advancement of the regulatory objectives. The study will also draw on lessons from the way the United Kingdom has used the regulatory sandbox as a tool in fostering financial inclusion. The research establishes the effects of the of a supranational model of the regulatory sandboxes and the challenges that are encountered when creating a cross border/cross jurisdictional sandbox. Finally, it makes recommendations on practical solutions that can be implemented to improve the effectiveness of the regulatory sandboxes in South Africa.